2010
DOI: 10.1007/bf03262743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep bruxism in a group of Brazilian schoolchildren

Abstract: The high prevalence of 35.3% demonstrates the need for further research on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
3
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 15 publications
4
76
3
14
Order By: Relevance
“…4,5,8,[15][16][17] The difficulty in diagnosing this parafunctional disturbance, mainly based on polysomnography exams, which was not performed in this sample, is known, 2 and it becomes even more limited when one is dealing with children at the stage of primary dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,8,[15][16][17] The difficulty in diagnosing this parafunctional disturbance, mainly based on polysomnography exams, which was not performed in this sample, is known, 2 and it becomes even more limited when one is dealing with children at the stage of primary dentition.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[16][17][18][19] The literature has demonstrated a significant frequency of this habit compared with temporomandibular dysfunctions, which are less prevalent in this age group. 12 However, there are studies that have found lower frequencies, ranging from 5.9% 1,20,21 to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…7 A previous study found that this disorder was more prevalent among children from families with a better socioeconomic status. 11 Although this association has not yet been clarified, it may be related to the number of daily activities children perform, an issue that needs to be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…1 The aetiology and characteristics of bruxism have not yet been well defined. 2 However, studies point to different associated risk indicators, such as local, psychological, genetic, neurological, systemic and social factors.…”
Section: Introductionmentioning
confidence: 99%